Influence of Annealing Temperature on Optical Properties of Al Doped ZnO Nanoparticles via Sol-gel Methods - Abd Rashid, AR; Hazwani, TN; Mukhtar, WM; Taib, NAM (Amer Inst Physics, 2024)
Zinc oxide (ZnO) thin films have become technologically important materials due to their wide range of electrical and optical properties. The characteristics can be further adjusted by adequate doping processes. The effect of dopant concentration of Al, heating treatment and annealing in reducing atmosphere on the optical properties of the thin films is discussed. Undoped and aluminum-doped zinc oxide (AZO) thin films are prepared by the sol-gel method. Zinc acetate dihydrate, 2-methoxyethanol and monoethanolamine are used as precursor, solvent and stabilizer. In the case of AZO, aluminum nitrate nanohydrate is added to the precursor solution with an atomic percentage equal to 0 %, 1 %, 2 % and 3 % of Al. The multi thin layers are transformed into ZnO upon annealing at 450 degrees C and 500 degrees C. The optical properties such as transmittance, absorbance, band gap and refractive index of the thin films have been investigated by using UV-Visible Spectroscopy (UV-Vis). The results show that the effect of aluminium dopant concentration on the optical properties is depend on the post-heat treatment of the films. By doping with Al, the transmittance spectra in visible range increased and widen the band gap of ZnO which might due to Burstein-moss effects.